Isolation of 11b-Hydroxycedrelone from Walsura yunnanensis and its Cytotoxic Activity - Jiang, Lihui (Asian Journal of Chemistry, 2015)
11b-Hydroxycedrelone was isolated from the twigs and leaves of Walsura yunnanensis C. Y. Wu. Its structure was established on the basis of spectroscopic methods. 11b-Hydroxycedrelone featured a typical rearranged A-ring structure of this compound class. Cytotoxic evaluation showed that its exhibited moderate inhibitory activity against HL-60 cell line with the IC50 values of 8.9 μM.